The Impact of Risk Aversion and Migrant Work Experience on Farmers’ Entrepreneurship: Evidence from China - Tong Wang; Jiaxuan Liu; Hongyu Zhu; Yuansheng Jiang (Agriculture, 2024)
Investing in entrepreneurship may be costly, and therefore risky, and entrepreneurship is also an economic endeavor that is highly dependent on entrepreneurial ability and risk appetite. In this study, data from 669 famers in southwest China were used as the sample, and we used three different methods to measure farmers’ risk aversion level, including DOSPRET (Domain-Specific Risk-Taking), SOEP (Simple Self-Report), and BRET (Bomb Risk Elicitation Task). This paper studies the impact of farmers’ risk aversion on entrepreneurial choices and the moderating impact of the migrant work experience (MWE) on the relationship between risk aversion and entrepreneurship. The results can be summarized as follows: Firstly, entrepreneurial farmers have lower average levels of risk aversion than non-entrepreneurial farmers. Secondly, risk aversion has a significant negative impact on farmers’ choice of entrepreneurship, corporate entrepreneurship and portfolio entrepreneurship. Thirdly, MWE can reduces the negative impact of risk aversion on a decision to enter entrepreneurship or portfolio entrepreneurship. Fourth, MWE in local or nearby areas reduces the negative effects of risk aversion on entrepreneurship and portfolio entrepreneurship, while MWE in coastal and developed cities increases the negative effects.